Synthesis of functional materials by non-Newtonian microfluidic multiphase system - Ren, Yong; Koh, Kai Seng; Zhang, Yaping (INTECH, 2016)
With increasing level of polymer solution involvement in multiphase microdevice for formation of emulsion and fabrication of functional materials, it is of paramount importance to systematically understand the relevant physics of droplet formation in non-Newtonian fluids and how the material formation process may be affected due to the complex rheological effect. The chapter aims to review and discuss the recent advances in echnologies that enable fabrication and application of functional materials formed from non-Newtonian microfluidic multiphase system. Rheological behavior of polymer solutions and the mathematical models are reviewed. The influence of microstructure on rheological behavior of polymer solutions and the fundamental physical phenomena driving non-Newtonian microfluidic multiphase system are discussed. Shear thinning and viscoelastic effect on breakup dynamics and droplet formation are presented. The microfabrication process of the device and synthesis of emulsion-templated materials with potential industrial and biochemical applications are elucidated.